Deteksi Dini Kualitas Tumbuh Kembang Anak Melalui Peningkatan Keterampilan Kader Kesehatan Terhadap Transformasi Layanan Primer Fokus Pada Pendekatan Pelayanan Kesehatan Kepada Masyarakat - Susanti, Susanti; Harahap, Nur Afifah; Batubara, Ardiana; Latifah, Latifah; Vandika, Arnes Yuli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The principle of child development refers to the basic guidelines and rules that guide the understanding and optimal care of children, with a focus on their physical, emotional, social, and cognitive growth and development. The purpose of Community Service is for Early Detection of the Quality of Child Growth and Development Through Improving the Skills of Health Cadres Towards the Transformation of Primary Services Focusing on the Approach of Health Services to the Community. The method used in Community Service activities is by providing materials, Q&A through discussion and training on Early Detection of the Quality of Child Growth and Development Through Improving the Skills of Health Cadres. by conducting tests before training (Pre Test) and after training (Post Test). The results of community service were obtained at the beginning of the observation of the skills of health cadres in carrying out child growth and development measurements, most were still lacking (65.31%) before being given training (Pre Test) and after training in measuring child growth and development, the skills of health cadres increased (Post Test), as many as 83.61% of health cadres were good at measuring child growth and development independently. The conclusion is that this health cadre training activity can provide benefits in developing community resources to support the health sector in efforts to improve public health.